Epinephrine Improves the Efficacy of Nebulized Hypertonic Saline in Moderate Bronchiolitis: A Randomised Clinical Trial. - J Carlos Flores-González; Miguel A Matamala-Morillo; Patricia Rodríguez-Campoy; Juan J Pérez-Guerrero; Belén Serrano-Moyano; Paloma Comino-Vazquez; Encarnación Palma-Zambrano; Rocio Bulo-Concellón; Vanessa Santos-Sánchez; Alfonso M Lechuga-Sancho; Bronchiolitis of Cadiz Study group (BronCaS) (PLoS ONE, 2015)
There is no evidence that the epinephrine-3% hypertonic saline combination is more effective than 3% hypertonic saline alone for treating infants hospitalized with acute bronchiolitis. We evaluated the efficacy of nebulized epinephrine in 3% hypertonic saline.We performed a randomized, double-blind, placebo-controlled clinical trial in 208 infants hospitalized with acute moderate bronchiolitis. Infants were randomly assigned to receive nebulized 3% hypertonic saline with either 3 mL of epinephrine or 3 mL of placebo, administered every four hours. The primary outcome measure was the length of hospital stay.A total of 185 infants were analyzed: 94 in the epinephrine plus 3% hypertonic saline group and 91 in the placebo plus 3% hypertonic saline group. Baseline demographic and clinical characteristics were similar in both groups. Length of hospital stay was significantly reduced in the epinephrine group as compared with the placebo group (3.94 ±1.88 days vs. 4.82 ±2.30 days, P = 0.011). Disease severity also decreased significantly earlier in the epinephrine group (P = 0.029 and P = 0.036 on days 3 and 5, respectively).In our setting, nebulized epinephrine in 3% hypertonic saline significantly shortens hospital stay in hospitalized infants with acute moderate bronchiolitis compared to 3% hypertonic saline alone, and improves the clinical scores of severity from the third day of treatment, but not before.EudraCT 2009-016042-57.